Psychoanalysis, history, and radical ethics : learning to hear - Orange, Donna M. (Milton : Routledge, 2019)
Psychoanalysis, History, and Radical Ethics: Learning to Hear explores the importance of listening, being able to speak, and those who are silenced, from a psychoanalytic perspective. In particular, it focuses on those voices silenced either collectively or individually by trauma, culture, discrimination and persecution, and even by the history of psychoanalysis. Drawing on lessons from philosophy and history as well as clinical vignettes, this book provides a comprehensive guide to understanding the role of trauma in creating silence, and the importance for psychoanalysts of learning to hear those silenced voices.
"Psychoanalysis, History, and Radical Ethics: Learning to Hear explores the importance of listening, being able to speak, and those who are silenced, from a psychoanalytic perspective. In particular, it focuses on those voices silenced either collectively or individually by trauma, culture, discrimination and persecution, and even by the history of psychoanalysis. Drawing on lessons from philosophy and history as well as clinical vignettes, this book provides a comprehensive guide to understanding the role of trauma in creating silence, and the importance for psychoanalysts of learning to hear those silenced voices"--
Cover; Half Title; Series Page; Title; Copyright; Dedication; Contents; Permissions; Introduction: learning to hear; 1 Silence in phenomenology: dream or nightmare?; 2 Violence, dissociation, and traumatizing silence; 3 This is not psychoanalysis!; 4 The seduction of mystical monisms in the humanistic psychotherapies; 5 Reading history as an ethical and therapeutic project; 6 Radical ethics: beyond moderation; 7 Ethical hearing: demand and enigma; Afterword; Index
Description based upon print version of record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Psychoanalysis and philosophy; Psychoanalysis -- Moral and ethical aspects; History -- Psychological aspects; Collective memory -- Psychological aspects; Silence -- Psychological aspects; Psychanalyse et philosophie; Mémoire collective -- Aspect psychologique; Histoire -- Aspect psychologique; Psychanalyse -- Aspect moral; Silence -- Aspect psychologique; History -- Psychological aspects; Psychoanalysis and philosophy; Psychoanalysis -- Moral and ethical aspects; Silence -- Psychological aspects